Nursing presence from the perspective of cancer patients: A cross-sectional study - Mahshid Mahdavi; Mansour Ghafourifard; Azad Rahmani (Tehran University of Medical Sciences, 2020)
Background & Aim: Nursing presence is an essential element of nursing care. Since the perception of nursing presence is influenced by different factors depending on the culture within which patients receive nursing care, this study aimed to investigate Iranian patients' nursing presence with cancer. Methods & Materials: In this cross-sectional study, 130 cancer patients were selected by random sampling from an oncology teaching hospital. Data was collected by the Presence of Nursing Scale and analyzed by SPSS software. Results: The results showed that the mean score of nursing presence (in a range of 0 to 125) was 101.91±16.19. According to the results, the highest and lowest scores belonged to the items "I trusted in these nurses" and "These nurses met my spiritual needs" with a mean score of 4.38±0.81 and 3.68±1.16, respectively. Data analysis by Pearson correlation coefficient showed no significant correlation between the mean score of nursing presence and quantitative variables such as patients' age, length of stay in the hospital, and the number of hospitalization (p>0.05). Conclusion: Although the total score of nursing presence was high, improvements in some items such as fulfilling the spiritual needs of cancer patients seem necessary. Evaluation of nursing presence by valid measures, encouraging nurses to spend more time and interacting with their patients, and providing special courses on nursing presence could help nurses improve and implement oncology nursing.